The crystal structure of 3-([1,1′-biphenyl]-2-yl)-1,2-diphenylbenzo[b]phosphole-1-oxide, C32H23OP - Yuan Chengxiong; Huang Mingqing; Liu Fen; Huang Haiyang (Zeitschrift für Kristallographie - New Crystal Structures)
C32H23OP, monoclinic, P21/n (no. 14), a = 9.1869(11) Å, b = 27.940(3) Å, c = 9.6992(11) Å, β = 107.422(2)°, V = 2375.4(5) Å3, Z = 4, Rgt(F) = 0.0486, wRref(F2) = 0.1255, T = 296 K.